Study of Aerosols’ Characteristics and Dynamics over the Kingdom of Saudi Arabia Using a Multisensor Approach Combined with Ground Observations - Ashraf Farahat; Hesham El-Askary; Abdulaziz Al-Shaibani (Advances in Meteorology)
This study covers various aspects of the aerosol distribution and characteristics, namely, optical depth climatology, absorption characteristics, and their microphysical properties over four regions in Saudi Arabia using satellite and ground observations including MODIS/Terra and Aqua, OMI, MISR/Terra, AERONET, and CALIPSO for the period April 2003–January 2013. The study includes cities in the North Western, Western, Eastern provinces of Saudi Arabia and in the Rub al Khali desert or Empty Quarter. Satellite and ground observations showed that the dust season extends from April to August with prominent peaks yet with high anthropogenic contribution late summer and early fall. Analysis shows an increase in the aerosol concentration during March 2009 which could be attributed to a major dust storm during that time. Comparing the AOD time series over regions 1–3 and region 4 (desert) we observe monthly and annual variability with no recurrence pattern over the years. The Aqua Deep Blue AOD550 data shows a single peak pattern that occurs over region 4 during the spring season known for its frequent dust events. OMI data shed the light on the presence of higher air pollution levels over region 3, representing the oil rich eastern province of Saudi Arabia.